Representations of climate security in COP27 dialogues on Twitter - Tucci, Giulia; Carneiro, Bia (CGIAR FOCUS Climate Security, 2022)
Between November 06-18,2022, Egypt hosted the 27th Conference of the Parties of the UNFCCC (COP27) in Sharm El-Sheikh. Considering the relevance of COP27 at a global level, and as a space for debates central to the research agenda of the CGIAR FOCUS Climate Security, this working paper leverages on digital methods approaches to assess public debates about the conference generated on Twitter. It aims to address two main questions: (i)What were the main trends related to COP27 debates, in relation to topics, sentiment and actors? (ii) How was climate security framed within these discussions?